RECENT DEVELOPMENTS IN INELASTIC NEUTRON-SCATTERING MEASUREMENTS ON METAL-HYDRIDES - Benham, M; Ross, D; Gilberd, P; Penfold, J; Taylor, A; Tompkinson, J; Bonnet, J (1987)
The authors describe a number of ways in which this improved instrumentation can be used to extend our understanding of metal-hydrogen systems. Thus for example we have used INlb to measure the scattering from alpha yttrium-hydrogen. The high intensity has enabled us to analyze the spectrum by fitting Gaussians. The peak at 100 meV due to the c direction vibrations of the proton is now split into two components. The temperature variation of the intensities of these sub-peaks can be related to the structural change that takes place in this system between minus 100 and plus 100 degree C. The positions and intensity of the various harmonics also yield information on the anharmonicity of the potential well.